The proteomics behind clinical and temporal changes in Parkinson's Disease: a literature review - Silva, Valécia Natália Carvalho da (2022)
Parkinson's disease (PD) is characterized by the dopaminergic neuron's progressive neurodegeneration, which is chronic and results in movement and behavioral disorders. There are still many gaps in the PD etiology and pathogenesis. Thus, aiming to strengthen the evidence that serves as a tool for diagnostic aid and future treatments, this systematic review aims to relate and analyze studies on the PARK proteomics, that is, the class of expressed park proteins that are associated with pathogenesis, PD clinical changes, and temporal effects. 261 papers were selected for eligibility analysis based on their title and abstract, resulting in 56 papers, with a full reading, included in this study. The observed result leads to the understanding of gene expression for a class of proteins that participate in cellular metabolic pathways associated with the PD etiology. Genetic studies applied to proteomics investigated disease-linked loci of PARK genes and their gene expression to relate the cellular pathways that contribute to PD. It was observed that PARK proteins corroborate the PD pathogenesis, highlighting the hypothesis of change in perception over time. Therefore, exploratory, and systematic studies can guide future investigations and strengthen clinically applied evidence.